PENGARUH FUNGSI KEPEMIMPINAN, KUALITAS SUMBER DAYA MANUSIA, DAN PERENCANAAN TERHADAP KINERJA TIM PENGELOLA REHABILITASI DAN REKONSTRUKSI PASCA GEMPA 30 SEPTEMBER 2009 DI PROPINSI SUMATERA BARAT - Dewi Meilda Eka Sari; Ali Anis (Jurnal Riset Manajemen Bisnis dan Publik, 2013)
The purpose of this research is to find out that the function of leadership, the quality of human resources and the planning influence to the performance of the manager team of rehabilitation and reconstruction West Sumatra September 30th 2009 Earthquake. The function of leadership will improve the quality of human resources. The function of leadership supported by the quality of human resource, the planning will be the better prepared. The function of leadership, high quality human resources and good planning will improve the performance of the management team of rehabilitation and reconstruction after the earthquake 30 September 2009. The conclusion find out that is the function of leadership, the quality of human resources and the planning contributing influence manager team in rehabilitation and reconstruction West Sumatra September 30th 2009 Earthquake.   Keyword: Leadership Function, Human Resources Quality, Planning and Performance